(untitled) (Indian Journal of Arid Horticulture, 2016)
Date palm is one of the important arid fruit crops, naturally propagated through offshoots and seeds. These methods of propagation are not sufficient to meet the demand of genetically uniform large scale plantation of female date palm plants. This demand has been realized through tissue culture methods; embryogenesis and organogenesis. Initially somatic embryogenesis (SE) protocols have been developed for several cultivars of date palm in different countries for its large scale multiplication and planted in the field. After noticing abnormalities in some of the date palm plants developed through SE due to somaclonal variations, organogenesis method has been developed though it has low multiplication rate. Now-a-days date palm is commercially produced by organogenesis method in Morocco, UAE and Saudi Arabia. Research focus has also been given on identification of somaclonal variations in date palm plants produced by SE method by molecular markers, increasing multiplication rate in organogenesis method by modifying cultural conditions, automation of protocols, identification of exact cells involving in embryo formation and their mechanisms, etc. In India, recently SE protocol developed by public sector for commercial use and several public and private sectors involved in production of date palm plants by tissue culture approach. However many challenges ahead still needs to be resolved are; precise identification of somaclonal variants in in vitro, increasing multiplication rate in organogenesis, reducing duration in juvenile phase for callus induction in SE and shoot bud formation in organogenesis, developing genotype independent tissue culture protocols.